2021
DOI: 10.1007/s00435-021-00516-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the osteon morphology depend on the body mass? A scaling study on macroscopic and histomorphometric differences between cow (Bos taurus) and sheep (Ovis aries)

Abstract: The structure and geometry of bone depend on many biological and environmental factors. These factors affect the bone tissue's microstructure differently, and their interaction has not yet been fully elucidated. Our research investigated the effect of body mass on the macro- and microstructure of the compact bone. Therefore we analyzed the humerus and femur bones from females of 11 cows and 11 sheep at the age of 4–10 years. Both species have very similar dietary and locomotion patterns, but their body size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These results evidenced the relationships between structure and function in bone tissue, and the importance of local strain measurements to describe and 620 assess the elastic instabilities of bone structure that cannot be entirely described by the material properties of the tissue. However, such relationships were difficult to observe in cortical bone specimens, mainly due to the coarse DVC-resolution (~300 μm), approximately double than the diameter of the osteons in bovine femur [92]. Osteons are complex mechanical features that can act both as stress concentrators, where cracks may initiate 625 (Figure 9a), or as crack propagation barriers (Figure 9b, c).…”
mentioning
confidence: 99%
“…These results evidenced the relationships between structure and function in bone tissue, and the importance of local strain measurements to describe and 620 assess the elastic instabilities of bone structure that cannot be entirely described by the material properties of the tissue. However, such relationships were difficult to observe in cortical bone specimens, mainly due to the coarse DVC-resolution (~300 μm), approximately double than the diameter of the osteons in bovine femur [92]. Osteons are complex mechanical features that can act both as stress concentrators, where cracks may initiate 625 (Figure 9a), or as crack propagation barriers (Figure 9b, c).…”
mentioning
confidence: 99%
“…Furthermore, since osteons showing an elliptical shape have been supposed typical of animal species with pronounced locomotor activity (e.g. mouflon compared to sheep (Giua et al 2014), goat compared to sheep (Zedda et al 2017), wild boar compared to domestic pigs (Zedda et al 2019), and wild horse compared to domestic horse (Zedda et al 2020)), the almost circular shape of the Bate individual osteons could suggest poor performance during fast and agile movements (Zedda et al 2008(Zedda et al , 2015Zedda & Babosova 2021;Skedros et al 2013), as already inferred by the morphological features shown by the autopodium bones (Caloi & Palombo 1995.…”
Section: Unique Individualmentioning
confidence: 83%
“…2020)), the almost circular shape of the Bate individual osteons could suggest poor performance during fast and agile movements (Zedda et al . 2008, 2015; Zedda & Babosova 2021; Skedros et al . 2013), as already inferred by the morphological features shown by the autopodium bones (Caloi & Palombo 1995, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…( D ) Canis lupus familiaris bone structure: a high density of medium size osteons, with a central canal (1) and osteocytes (2), and a great number of interstitial systems (image adapted from Morales et al [ 57 ]). ( E ) Bos taurus bone structure: dense Haversian tissue with a big osteon with a central canal (1) and osteocytes (2) (image adapted from Zedda et al [ 67 ]). ( F ) Sus scrofa bone structure: plexiform tissue, osteocytes (2) surrounded by lacunas (image adapted from Zedda [ 68 ]).…”
Section: Human Bone Vs Non-human Bonementioning
confidence: 99%